Service-Learning in Teacher Education: Does the Model Matter? - Castellan, Catherine M. (International Journal of Research on Service-Learning in Teacher Education, 2013)
The purpose of this qualitative study was to gain an understanding of the sense freshmen elementary education majors made of their service-learning experiences in their teacher education courses. Data were gathered from six majors over two semesters, three who engaged in a regular model of service-learning and three in a cascading model. Findings indicated that the service-learning experiences reinforced the majors learning of course content and suggest that the type of service-learning model has an impact on the quality and depth of sense making and understanding of education on the part of future teachers. In their call for more integrated and coherent designs for teacher education programs, Darling-Hammond, Grossman, Hammerness, Rust, and Shulman (2005) suggest that teacher education programs should make effective connections among courses and stronger links between clinical experiences and formal coursework. When provided early and throughout the program, they argue, clinical experiences allow learners to develop conceptual frameworks that assist them in organizing, conceptualizing, and better understanding the theories and ideas presented in their academic work. The authors claim that students who have some experience with teaching, including clinical experiences, are more prepared to make sense of their academic work and that the academic theories and ideas can in turn help them make sense of experiences and observations. To advance our understanding of the effectiveness of this integration of academic work and clinical experiences such as service-learning, this study collected and analyzed in-depth qualitative data from six freshman elementary education majors to examine the sense they made of their service-learning experiences as part of their first-year teacher education courses. Although most of the students in the instructor/researchers previous courses had quantitatively indicated that their service-learning experiences had helped them learn the course content, this study was undertaken to gain greater insight into this process. This study adopted a constructivist perspective by attempting to focus on the meaning participants made through an active, social construction of knowledge, rather than recall of information (Brooks & Brooks, 1993). The primary research question driving this study was, what sense did freshman elementary education majors make of their service-learning experiences in their teacher education courses? Because the participants in the study engaged in two different models of service-learning, the data analysis also examined similarities and differences in the sense-making of the participants in the two models, which is the primary focus of this article.